Google Translate In Pronouncing And Providing Phonetic Transcription - Azra Batrisyia Sabrina; Sirrul Aulia; Yani Lubis (Pusat Riset dan Inovasi Nasional, 2023)
The research aims to find out the effectiveness of Google Translate in pronouncing English words and providing the Phonetic Transcription from university students’ perspective. This is qualitative research that uses questionnaires directed to the students and observation by the researchers to collect the result. It turns out that Google Translate provides accurate pronunciation after being compared to other translation tools, but it’s not provide the Phonetic Transcription which students’ know so.